2018
DOI: 10.1002/ctpp.201800020
|View full text |Cite
|
Sign up to set email alerts
|

Dust‐ion‐acoustic solitary waves in a magnetized dusty pair‐ion plasma with Cairns‐Gurevich electrons and opposite polarity dust particles

Abstract: The nonlinear dust-ion-acoustic (DIA) solitary structures have been studied in a dusty plasma, including the Cairns-Gurevich distribution for electrons, both negative and positive ions, and immobile opposite polarity dust grains. The external magnetic field directed along the z-axis is considered. By using the standard reductive perturbation technique and the hydrodynamics model for the ion fluid, the modified Zakharov-Kuznetsov equation was derived for small but finite amplitude waves and was provided the sol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…They showed that non‐extensivity parameter and dust concentration play a crucial role in the evolution of non‐linear and super‐nonlinear DIA waves. Abdikian [ 32 ] investigated DIA solitary waves in a magnetized dusty pair‐ion plasma with opposite polarity of dust grains, and showed the effects of plasma parameters on the existence of solitary waves through the phase portraits analysis of the dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…They showed that non‐extensivity parameter and dust concentration play a crucial role in the evolution of non‐linear and super‐nonlinear DIA waves. Abdikian [ 32 ] investigated DIA solitary waves in a magnetized dusty pair‐ion plasma with opposite polarity of dust grains, and showed the effects of plasma parameters on the existence of solitary waves through the phase portraits analysis of the dynamical system.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al [ 29 ] illustrated that the amplitude and the width of negative potential DA soliton profiles increase with the decrease in polarization force. Abdikian [ 30 ] examined the non‐linear behaviour of dust‐ion‐acoustic solitary structures in a dusty plasma, including both negative and positive ions with the Cairns‐Gurevich distribution for electrons and immobile opposite polarity dust particles. Abdikian [ 30 ] illustrated that dust‐ion‐acoustic soliton energy increases with the increase of the trapping parameter for electrons.…”
Section: Introductionmentioning
confidence: 99%
“…Abdikian [ 30 ] examined the non‐linear behaviour of dust‐ion‐acoustic solitary structures in a dusty plasma, including both negative and positive ions with the Cairns‐Gurevich distribution for electrons and immobile opposite polarity dust particles. Abdikian [ 30 ] illustrated that dust‐ion‐acoustic soliton energy increases with the increase of the trapping parameter for electrons. Recently, Demiray and Abdikian [ 31 ] applied the non‐linear field equations of hot dusty plasma in the presence of nonthermal electrons and trapped ions.…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have tried to find effects of trapped particles in plasma on the genesis and propagation of solitary wave features [38][39][40]. Very recently, by applying the RPT and hydrodynamic model equations for the ion fluid, Abdikian [41] has studied the nonlinear DIA solitary waves in magnetized dusty plasmas with negative and positive ions, and stationary opposite polarity dust particles. By considering the Cairns-Gurevich distribution for electrons, the author has derived the modified ZK equation and discussed how the different plasma parameters have an influence on the solitary wave features.…”
Section: Introductionmentioning
confidence: 99%